(untitled) (Training and Practice : Journal of Educational Sciences, 2007)
Gender equality in science appears in many fields such as the selection of research topics, the examination of societal aspects of the research process and the research results and the career of the researchers themselves. Although gender equality in research and development has been studied since the 1970’ in the US and equal opportunities belong to its principles, the European Union started to prioritise this issue only in the last decade. In Hungary this topic doesn’t belong to the priorities yet. The proportion of women among scientists in Hungary is higher than the EU average, but this does not mean that there are equal opportunities for women and men in research and development. This article contains a chapter of my PhD thesis that I defended recently, in which I analyse the results of my empirical research. The main finding is that even though the scientific society is quite controversial about this topic, the vast majority of female researchers with a scientific degree working in the public sector think that women and men have no equal opportunities in R&D in Hungary.